Enhancing Ethical Awareness Among Nursing Students in the Digital Age to Prevent Code Violations - Angelina Azi Meze; Dewi Yustiani; Dwi Rejeki Manoppo; Latifatul Umaroh (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
The rapid advancement of digital technology in healthcare has transformed the way nursing students access information, communicate, and practice clinically. While digitalization offers numerous benefits, it also introduces ethical challenges related to confidentiality, professionalism, and online conduct. This study explores the role of ethical education in helping nursing students prevent ethical code violations in the digital era. A qualitative descriptive approach was used, with data collected from 15 nursing students through semi-structured interviews and document analysis. The findings indicate that ethical education enhances students' ethical reasoning, digital responsibility, and awareness of legal implications. Participants reported that ethical education enabled them to critically reflect on their actions, particularly in online environments where ethical boundaries are often ambiguous. The study emphasizes the importance of integrating ethical values continuously throughout the nursing curriculum, rather than treating it as a standalone course. Key factors such as institutional support, curriculum relevance, and educator role modeling were identified as essential in promoting ethical behavior. The results underscore the need for enhanced ethical education in nursing programs to ensure that graduates are not only clinically proficient but also ethically responsible in their digital and professional interactions.